A broadband U‐shaped patch antenna on PTFE/Cu substrate for 60 GHz wireless communications. Issue 1 (1st December 2017) - Adane, Amar; Person, Christian; Gallee, François
Abstract: A U‐shaped antenna is printed on polytetrafluoroethylene film, deposited on a copper base having air cavity inside, using thin film micro‐strip technology. This antenna is as compact as the rectangular patch and covers the 51.5–62 GHz band. Unlike the silicon substrate, its metallic support yields better radiation patterns.